Evaluation of dietary incorporation of treated waste silkworm pupae meal on nutrient utilization and performance of broiler chicken - AANVI; SHARMA, RAMESH KUMAR; KHAN, NAZAM; RASTOGI, ANKUR; PATHAK, ANAND KUMAR; SHARMA, VIJAY KUMAR (The Indian Journal of Animal Sciences, 2025)
The most expensive component in poultry feed formulations is protein of animal origin. Considerable emphasis is placed on exploring alternative protein sources to reduce feeding costs. In this context, the present study evaluated the effect of incorporating ethanol-treated waste silkworm pupae meal (WSWPM-ET) in broiler chicken diets on their production performance, carcass characteristics, immunological responses, and blood-biochemical profile. The proximate composition of WSWPM-ET (on dry matter basis) was as follows: crude protein (CP) 51.97 ± 0.67%, ether extract (EE) 9.23 ± 0.06%, crude fiber (CF) 4.58 ± 0.28%, total ash (TA) 4.89 ± 0.07%, nitrogen-free extract (NFE) 29.31 ± 0.79%, calcium (Ca) 0.23 ± 0.01% and phosphorus (P) 0.90 ± 0.01%. Notably, the EE content of the untreated sample was 37.43%, indicating that the treatment method employed was effective in achieving the desired partial defatting. A total of 225 day-old broiler chicks were randomly allocated into five groups, each consisting of three replicates of 15 chicks. The control (C) group was fed a basal diet, while the treatment groups (T1, T2, T3, and T4) received diets in which meat and bone meal (MBM) was replaced with WSWPM-ET at 25%, 50%, 75%, and 100% levels, respectively. At the conclusion of the 42-day growth trial, two birds from each replicate were slaughtered for carcass evaluation. The findings suggest that WSWPM-ET can successfully replace MBM up to 75% in broiler rations without any adverse effects on growth performance, health status, or production traits.